Analysis with ultrasmall numbers - Hrbacek, Karel, 1944-; Lessmann, Olivier; O'Donovan, Richard (Richard John), 1953- (Textbooks in mathematics (Boca Raton, Fla.), 2015)
Analysis with Ultrasmall Numbers presents an intuitive treatment of mathematics using ultrasmall numbers. With this modern approach to infinitesimals, proofs become simpler and more focused on the combinatorial heart of arguments, unlike traditional treatments that use epsilon-delta methods. Students can fully prove fundamental results, such as the Extreme Value Theorem, from the axioms immediately, without needing to master notions of supremum or compactness. The book is suitable for a calculus course at the undergraduate or high school level or for self-study with an emphasis on nonstandard.